The Perilous Road Towards World Society (?): Global South in The Russo-Ukraine War - Diandra Ayu Larasati (Global South Review, 2022)
This paper addresses the lukewarm reaction exhibited by most of the Global South (GS) states regarding the Russo-Ukraine war. Despite the massive campaigning from the West for the world to side with Ukraine and go against Russia, only a few of the GS states follow through with this narration. Most of them choose to pledge neutrality instead, which is unexpected if one considers that the majority of the GS also experienced military aggressions and occupations in the past. By employing qualitative research methods, this paper is written to provide an interpretation of this phenomenon through the English School perspective, precisely its argument regarding the concepts of the ‘International System,’ ‘International Society,’ and ‘World Society’ spectrum. This paper finds that this condition happens because the GS perceives the Russo-Ukrainian conflict as an ‘alien’ conflict largely detached from the GS’ own international society, which has a separate model of interactions built upon a long span of historical events unrelated to both Russia and Ukraine. This sense of viewing the conflict as ‘foreign’ emerges from the perspective of this conflict being fought amongst the ‘Global North’ states. This means that both belligerents are conceptually equal in terms of being actors from ‘outside’ the international society of the GS. Other than that, the GS also has shared norms that go against the interventionist policies advocated by the GN states. However, the loose notion of ‘World Society’ is still viable, as, despite the North-South divide, both societies share the expected value of a nation-state’s sovereignty.